Evaluating the Combined Effect of Strategy, Brand and Country of Origin on Consumers’ Perceptions of Global Products - Kovalenko, Oksana (2012)
Abstract Key words: brand, country of origin, local brands, global brands, consumer perception, self-identity, lock-in strategies, first mover advantage, resource based view.